Study of serum uric acid levels in type 2 diabetes mellitus in tertiary care hospital in south Gujarat - Panchani, Mit; Dutt, Neha; Dhangar, Vandana; Dandge, Vinod (International Journal of Advances in Medicine, 2021)
Background: The need for early indicators of diabetic complications is essential to prevent late complications and their deleterious effects. There is a need for sensitive serum markers that are associated with diabetes and its complications. Estimation of these parameters helps in early intervention, thereby delaying the chronic complications of diabetes in the early stages. Hyperuricemia has been shown to be linked to a number of diseases and conditions including gout, hypertension, cardiovascular disease, myocardial infarction, stroke and renal disease. Uric acid has long been associated with delayed complications of diabetes mellitus. This study was conducted on 357 patients of diabetes mellitus to investigate the significance of serum uric acid levels and its correlation with it. Methods: This is an observational cross-sectional study carried out amongst 357 patients with T2DM attending out-patient department as well as indoor patients under medicine department at Surat Municipal Institute of Medical Education and Research (SMIMER) Hospital, of south Gujarat. Results: There is highly significant association seen between HbA1c (glycated hemoglobin) and uric acid levels in present study (p<0.001). There is significant association seen between fasting blood sugar (FBS) levels and uric acid levels in the study (p=0.0253). Conclusions: There is increase in uric acid levels in diabetic patients with increased levels of HbA1c. Thus, serum uric acid may serve as a potential biomarker of the deterioration of glucose metabolism.